Hubungan antara self efficacy dengan kepatuhan minum obat hipoglikemik oral pada penderita dm tipe ii : Relationship between self efficacy with medication adherence in patients with type ii dm - Pramesti, Theresia Anita; Saraswati, Dewa Ayu Lilik; Wardhana, Zainal Firdaus (Bali Medika Jurnal, 2021)
The success of preventing the complications of diabetes mellitus can be achieved through medication adherence in the use of oral hypoglycemic drugs. The success of a treatment in DM patients depends on the ability and high confidence in the patient, or what is called Self efficacy. The aimed of this study to determined the relationship of Self efficacy with adherence to taking oral hypoglycemic drugs in patients with type II diabetes mellitus. The research design used descriptive correlational with cross sectional design. The sampling technique used consecutive sampling with a sample of 60 people with type II DM. The results showed 25 people (41.7%) had high Self efficacy and 31 people (51.7%) had oral hypoglycemic medication adherence in the high category. Spearman Rank test results with α = 0.05 obtained p value = 0,000 and correlation coefficient (r) = 0.936 which means there is a strong relationship between Self efficacy with adherence to taking oral hypoglycemic drugs with the strength of strong relationships and positive direction. Self efficacy will affect the ability to adjust, understand and recognize the problems faced and motivate patients to change behavior, one of which is medication adherence.